Mereformulasi Pedagogi Matematika: Pendekatan Pembelajaran Berbasis Masalah untuk Menumbuhkan Keterlibatan Aktif Peserta Didik Madrasah Ibtidaiyah: - - Moch. Farich Alfani; Putri Sekar Sari; Andi Prastowo (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
Contemporary education seeks to cultivate in students a repertoire of essential competencies, including problem-solving, collaboration, critical thinking, creativity, and effective communication. In this context, it is imperative that educators adopt pedagogical strategies that actively engage learners in the construction of knowledge. Problem-Based Learning (PBL) has emerged as a pedagogical approach capable of fostering active learner participation while simultaneously enhancing problem-solving and critical thinking abilities. This study examines the effectiveness and contextual suitability of PBL in mathematics instruction as a means of promoting active student engagement. The research was conducted at a State Islamic Elementary School (Madrasah Ibtidaiyah Negeri) in Bantul District, Yogyakarta, involving a cohort of 30 fifth-grade students and their classroom teacher. Employing a qualitative methodology within a case study framework, the investigation drew upon multiple sources of evidence, including interviews, classroom observations, documentary analysis, and visual records. Data were processed using an interactive analytical model encompassing data condensation, data display, and conclusion drawing. Findings indicate that the integration of PBL into mathematics teaching substantively enhances students’ active participation in the learning process. Moreover, PBL constitutes an effective pedagogical vehicle for advancing the objectives of Indonesia’s independent curriculum within the context of elementary madrasahs